Stress Reshapes the Physiological Response of Halophile Fungi to Salinity - Pérez-Llano, Yordanis (Cells, 2020)
(1) Background: Mechanisms of cellular and molecular adaptation of fungi to salinity have been commonly drawn from halotolerant strains and few studies in basidiomycete fungi. These studies have been conducted in settings where cells are subjected to stress, either hypo- or hyperosmotic, which can be a confounding factor in describing physiological mechanisms related to salinity. (2) Methods: We have studied transcriptomic changes in Aspergillus sydowii, a halophilic species, when growing in three different salinity conditions (No NaCl, 0.5 M, and 2.0 M NaCl). (3) Results: In this fungus, major physiological modifications occur under high salinity (2.0 M NaCl) and not when cultured under optimal conditions (0.5 M NaCl), suggesting that most of the mechanisms described for halophilic growth are a consequence of saline stress response and not an adaptation to saline conditions. Cell wall modifications occur exclusively at extreme salinity, with an increase in cell wall thickness and lamellar structure, which seem to involve a decrease in chitin content and an augmented content of alfa and beta-glucans. Additionally, three hydrophobin genes were differentially expressed under hypo- or hyperosmotic stress but not when the fungus grows optimally. Regarding compatible solutes, glycerol is the main compound accumulated in salt stress conditions, whereas trehalose is accumulated in the absence of salt. (4) Conclusions: Physiological responses to salinity vary greatly between optimal and high salt concentrations and are not a simple graded effect as the salt concentration increases. Our results highlight the influence of stress in reshaping the response of extremophiles to environmental challenges.